A survey of the clinical practice followed by Korean medicine doctors for scoliosis: Preliminary data for clinical practice guidelines. Issue 34 (26th August 2022) - Sung, Won-Suk; Choi, Seong-Kyeong; Jo, Hyo-Rim; Park, Seo-Hyun; Lee, Sun-Haeng; Lee, Yoon-Jae; Ha, In-Hyuk; Seo, Byung-Kwan; Yang, Hoe-Cheon; Hong, Seung-Ug; Keum, Dong-Ho; Kim, Eun-Jung
Abstract : Scoliosis is a spinal disease in which the Cobb angle is >10°. Scoliosis treatment can be surgical or conservative, and clinical practice guidelines (CPGs) for conservative treatments have been updated since 2006. There have been several articles regarding the efficacy and safety of Korean medicine (KM) in treating scoliosis, but there are no CPGs. Our study investigated the current clinical practice using a survey for the future establishment of KM-CPGs. The survey mainly comprised clinical practice status, diagnosis, treatment, progress and prognosis, and perception of KM on scoliosis, with reference to existing surveys of other musculoskeletal disorders and scoliosis-related articles. A web-based survey was conducted from February 16, 2021 to February 28, 2021. We found that 60% of KM doctors (KMDs) respondents treated patients with scoliosis, and they valued radiographical measurements and scoliosis-related factors in the diagnosis. KMDs used multiple KM treatments, including acupuncture, Chuna, cupping, pharmacopuncture, and herbal medicine, and they emphasized the importance of KM more in nonstructural scoliosis than in structural scoliosis. Although the perception of the prognosis of scoliosis was in agreement with that suggested by previous guidelines, KMDs showed outstanding focus on reduction of symptoms of scoliosis and improvement of quality of life. Despite some limitations, including low participation and the need for consulting other medical practitioners, our study may be helpful for the development of KM-CPGs because it is the first to analyze the perceptions of KMDs on scoliosis and to collect preliminary data that are of significance for preparing clinical guidelines.